The hidden battles facing public safety IT managers. - Careless J (EMS Magazine, 2010)
Computers aren't the first things that come to mind when you think of EMS operations, but in today's high-tech world, proper information technology (IT) management is vital to keeping public safety agencies connected working safely. Like their frontline counterparts parts, EMS IT managers have their own battles to fight against tight budgets, incompatible equipment and harsh weather conditions. To get a sense of what they're up against, EMS Magazine interviewed three managers i Miami, Detroit and Seattle.